2020
DOI: 10.3354/meps13490
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns of benthic-pelagic coupling in oyster habitats

Abstract: Oysters enhance benthic-pelagic coupling in coastal systems by moving large quantities of suspended particulates to the sediments, stimulating biogeochemical processes. Recent research efforts have focused on quantifying the impact of oysters on coastal biogeochemical cycling, yet there is little consensus on how oysters influence processes across systems. A potential driver of this variance is availability of organic material suspended in the water column and subsequent loading to sediment by oysters. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…CO 2 release was unexpectedly low in the fall when sediment organic matter was again high (3.65 ± 1.22%) and temperature was higher than that in the spring (17.9 ± 0.6 °C). This observation may possibly be due to organic matter of a relatively lower quality in fall than that in the spring . Neither sediment organic matter ( p = 0.756, R 2 = 0.002, and df = 41) nor temperature ( p = 0.319, R 2 = 0.021, and df = 48) was a good predictor of sediment CO 2 release in the seasonal study.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…CO 2 release was unexpectedly low in the fall when sediment organic matter was again high (3.65 ± 1.22%) and temperature was higher than that in the spring (17.9 ± 0.6 °C). This observation may possibly be due to organic matter of a relatively lower quality in fall than that in the spring . Neither sediment organic matter ( p = 0.756, R 2 = 0.002, and df = 41) nor temperature ( p = 0.319, R 2 = 0.021, and df = 48) was a good predictor of sediment CO 2 release in the seasonal study.…”
Section: Resultsmentioning
confidence: 83%
“…The seasonal patterns of CO 2 and N 2 O fluxes we observed are consistent within the context of seasonal patterns of phytoplankton productivity in Narragansett Bay, which has historically been characterized by a large winter–spring diatom bloom and lower productivity during the summer. , If oysters drive sediment GHG production by increasing organic matter deposition to the sediments during filter-feeding, it might be expected that the highest GHG fluxes will occur following large phytoplankton blooms. We were able to test this hypothesis in our seasonal incubations as the spring sediment core incubation was conducted shortly after the winter–spring bloom, summer core incubations were conducted following a period of low productivity, and fall core incubations were conducted following a smaller fall bloom . This water-column production impacted the sediments as we measured the highest sediment % organic matter in the spring (3.97 ± 1.00%) followed by the fall (3.65 ± 1.22%) and lowest % organic matter in the summer (2.74 ± 0.57%).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the oyster production in the bay is in a crisis due to the lack of feed phytoplankton, and recently, it has been observed that the oyster larvae cannot survive due to the lack of small-sized phytoplankton (<5 µm in diameter) suitable for their feed [43]. In contrast, oysters, through their feeding activity, stimulate biogeochemical processes in the sediments by increasing the sedimentation of organic matter from the water column [44,45]. Therefore, the sediment quality is muddy and contains vast amounts of refractory organic matter which have been historically deposited from the oyster culture via both oyster feces and dead oyster meat, and organisms attached on the shells sink to the bottom.…”
Section: Introductionmentioning
confidence: 99%